Student Perspective: Margaret Chase Smith Library 2010 Student Essay Contest - Richards, David; Ruoux, Kacie (Maine Policy Review, 2010)
Each year the Margaret Chase Smith Library sponsors an essay contest for Maine high school seniors. The topic for 2010 was national health care, which has been part of public policy considerations since the end of World War II. In light of the current debate, students were invited to offer their opinions on what they think ought to be done to reform and improve the American medical system. We feature here the first place prize winning essay by Kacie Rioux, “Healthcare Reform for a New Era,” introduced by David Richards of the Margaret Chase Smith Library.
Keywords: healthcare reform